The effects of involuntary exposure of children to passive smoking: Integrative review (Research, Society and Development, 2023)
Objective: To analyze the impact of involuntary exposure of children to secondhand smoke. Methodology: The integrative review method was used with a search in scientific databases, to be mentioned; SciELO and LILACS. Results: A total of 194 studies were identified, and after filtering by eligibility criteria, the sample consisted of 10 studies. The toxicity of cigarette smoke that remains in the environment, even without the presence of a smoker, triggers numerous damages on childrens health and contributes to the worsening of already existing conditions, just being in the presence of a small amount of smoke is enough to have deleterious effects. There was an association between exposure to cigarette smoke and respiratory problems in this public, in addition to the direct impact on learning and the ability to gain excess weight at a preliminary age. Final considerations: There is a need to develop research aimed at families that have children in the presence of smokers, so that they are properly guided regarding this issue.